'Don't mess with my company': An exploratory study of commitment profiles before and after dramatic external events. (23rd February 2017) - Arciniega, Luis M.; Allen, Natalie J.; González, Luis
Abstract: This panel study, conducted in a large Venezuelan organization, took advantage of a serendipitous opportunity to examine the organizational commitment profiles of employees before and after a series of dramatic, and unexpected, political events directed specifically at the organization. Two waves of organizational commitment data were collected, 6 months apart, from a sample of 152 employees. No evidence was found that employees' continuance commitment to the organization was altered by the events described here. Interestingly, however, both affective and normative commitment increased significantly during the period of the study. Further, employee's commitment profiles at Wave 2 were more differentiated than they were at Wave 1.